Optimal medical therapy as a foundational strategy in simultaneous cardiocerebral infarction: A case series - Utama, Riawati; Suryono, Suryono; Candra Dewi, Yulia (Heart Science Journal, 2026)
Background: Cardiocerebral infarction (CCI), the simultaneous onset of acute myocardial infarction (AMI) and acute ischemic stroke (AIS), is a rare but fatal condition. Management is challenging due to a serious therapeutic dilemma: common reperfusion techniques for the heart and brain pose significant risks to other organ systems. This clinical contradiction, along with the high mortality rate, demonstrates how crucial it is to find a good way to deal with this situation. Case Illustration: This report describes two male patients, aged 69 and 66, who experienced concomitant ST-elevation myocardial infarction (STEMI) and acute ischemic stroke (AIS). The first patient was treated conservatively with complete optimal medical care (OMT) after the family declined primary percutaneous coronary intervention (PCI). The second patient, whose hemodynamics were stable, underwent PCI in addition to the same OMT treatment. Fibrinolytic treatment is not an option in any case. The OMT plan requires two antiplatelet medications, a statin, a beta-blocker, an anticoagulant, and a nitrate. Conclusions: Although the two patients underwent different types of treatment, both were discharged after seven days in the hospital in stable condition. These results demonstrate that a well-executed OMT regimen can serve as an important and fundamental approach that can provide beneficial short-term outcomes in CCI. OMT can serve as a stabilizing bridge to intervention or, in some cases, as an adequate final treatment.